ANALISIS PENILAIAN KINERJA KEUANGAN PADA KEDAI PLANEL - Uvi Alfianzyah; Yahya Nusa (JURNAL ULET (Utility, Earning and Tax), 2020)
The purpose of this study is to know the financial performance of the kedai Planel in fulfilling all its obligations and its ability to generate profits. The research method used is descriptive method. Data collection in this research was carried out using observation, interview, and documentation techniques. Measurement of the liquidity level of Planel cafe used current ratio and cash ratio, for the level of solvency used Debt to total assets ratio and Debt to Equity Ratio, and then for measuring the level of profitability used Net Profit Margin, Return On Assets and Return On Equity. The results showed that the financial performance of Planel cafe based on the level of liquidity was classified as good, the level of solvency was very good and the level of profitability was quite good.